2021
DOI: 10.1071/ch20260
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of RAFT Polymerization: Electrochemically Initiated RAFT Polymerization in Emulsion (Emulsion eRAFT), and Direct PhotoRAFT Polymerization of Liquid Crystalline Monomers

Abstract: We report on two important advances in radical polymerization with reversible addition–fragmentation chain transfer (RAFT polymerization). (1) Electrochemically initiated emulsion RAFT (eRAFT) polymerization provides rapid polymerization of styrene at ambient temperature. The electrolytes and mediators required for eRAFT are located in the aqueous continuous phase separate from the low-molar-mass-dispersity macroRAFT agent mediator and product in the dispersed phase. Use of a poly(N,N-dimethylacrylamide)-block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Multiblock copolymer synthesis via RDRP has become a prominent research topic since it was realized in 2011 for Cu(0)-mediated radical polymerization, and shortly thereafter for reversible addition–fragmentation chain transfer (RAFT) polymerization, that multiple consecutive polymer blocks can be grown for high conversion without intermittent purification under carefully considered conditions that guarantee high livingness (chain-end fidelity). In recent years, RDRP has been exploited for the synthesis of multiblock copolymers of increasing intricacy. ,,, RAFT polymerization, in particular, has proven itself highly viable for multiblock copolymer synthesis because of its good monomer compatibility, robustness to various polymerization techniques and conditions, superior performance in dispersed systems, and the large assemblage of accumulated interest and literature availablity. The synthesis of multiblock copolymers is characterized by the controlled polymerization of constituent monomers, with final material properties tailored via the block composition, length and sequence; such methodologies, however, lend themselves to certain complications. The issues with reduced chain-end fidelity, monomer compatibility, and long reaction times, while maintaining acceptable molecular weight distributions (MWDs), are obstacles that become even more pertinent as the block length and the number of involved monomer species increase.…”
Section: Introductionmentioning
confidence: 99%
“…Multiblock copolymer synthesis via RDRP has become a prominent research topic since it was realized in 2011 for Cu(0)-mediated radical polymerization, and shortly thereafter for reversible addition–fragmentation chain transfer (RAFT) polymerization, that multiple consecutive polymer blocks can be grown for high conversion without intermittent purification under carefully considered conditions that guarantee high livingness (chain-end fidelity). In recent years, RDRP has been exploited for the synthesis of multiblock copolymers of increasing intricacy. ,,, RAFT polymerization, in particular, has proven itself highly viable for multiblock copolymer synthesis because of its good monomer compatibility, robustness to various polymerization techniques and conditions, superior performance in dispersed systems, and the large assemblage of accumulated interest and literature availablity. The synthesis of multiblock copolymers is characterized by the controlled polymerization of constituent monomers, with final material properties tailored via the block composition, length and sequence; such methodologies, however, lend themselves to certain complications. The issues with reduced chain-end fidelity, monomer compatibility, and long reaction times, while maintaining acceptable molecular weight distributions (MWDs), are obstacles that become even more pertinent as the block length and the number of involved monomer species increase.…”
Section: Introductionmentioning
confidence: 99%
“…One defining trait of PI–RAFT is the reversible deactivation and the resulting increased chain end fidelity of the method when compared to conventional RAFT polymerization. While it was demonstrated that irreversible termination is still present, 37 in a typical PI–RAFT process reversible deactivation is deemed to be the main fate of growing radical. Indeed, it is even hypothesized that this mechanism is able to control a polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies are focused on the typical monomers involved in radical polymerization: methyl methacrylate, methyl acrylate, dimethylacrylamide, styrene, etc. [ 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Far less research has been conducted on the preparation of bottlebrush polymers through visible light-mediated polymerization.…”
Section: Introductionmentioning
confidence: 99%